A Systematic Review of Intravenous β-Hydroxybutyrate Use in Humans – A Promising Future Therapy? - White, Hayden; Heffernan, Aaron J.; Worrall, Simon; Grunsfeld, Alexander; Thomas, Matt (Frontiers in Medicine, 2021)
Therapeutic ketosis is traditionally induced with dietary modification. However, owing to the time delay involved, this is not a practical approach for treatment of acute conditions such as traumatic brain injury. Intravenous administration of ketones would obviate this problem by rapidly inducing ketosis. This has been confirmed in a number of small animal and human studies. Currently no such commercially available product exists. The aim of this systematic review is to review the safety and efficacy of intravenous beta-hydroxybutyrate. The Web of Science, PubMed and EMBASE databases were searched, and a systematic review undertaken. Thirty-five studies were included. The total beta-hydroxybutyrate dose ranged from 30 – 101 g administered over multiple doses as a short infusion, with most studies using the racemic form. Such dosing achieves a beta-hydroxybutyrate concentration > 1 mmol/L within 15 minutes. Infusions were well tolerated with few adverse events. Blood glucose concentrations occasionally were reduced but remained within the normal reference range for all study participants. Few studies have examined the effect of intravenous beta-hydroxybutyrate in disease states. In patients with heart failure, intravenous beta-hydroxybutyrate increased cardiac output by up to 40%. No studies were conducted in patients with neurological disease. Intravenous beta-hydroxybutyrate has been shown to increase cerebral blood flow and reduce cerebral glucose oxidation. Moreover, beta-hydroxybutyrate reduces protein catabolism and attenuates the production of counter-regulatory hormones during induced hypoglycemia. An intravenous beta-hydroxybutyrate formulation is well tolerated and may provide an alternative treatment option worthy of further research in disease states.